Something extraordinary : a short history of the Manhattan Project, Hanford, and the B Reactor - Ferguson, Robert L. (Robert Lewis); Smith, C. Mark (Of Richland, Washington) (Book Publishers Network, 2019)
From the history of atomic research to the continuing efforts to clean up the Hanford Site and the B Reactor (now part of the Manhattan Project National Historic Park), this book offers a concise but comprehensive narrative of the geopolitics and atomic research that led to the creation of the Manhattan Project-- the American effort to develop and deploy the atomic bomb during World War II. A key component was the development of the Hanford Site, where the plutonium used in America's atomic bombs was produced in the B Reactor there. Hanford and the B Reactor also played, and continue to play in the cleanup phase, an important role in the growth and economic fortunes of the nearby Tri-Cities communities. --Publisher.